Mô hình hợp tác giữa giảng viên và cán bộ thư viện tại các trường đại học - Nguyễn, Thị Lan (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article mentions the importance of the collaborative relationship between lecturers and librarians, as well as points out the outstanding teacher- librarians cooperation models in universities.